The Ways and Means of the Ukrainian Nation's Self-Determination: a Philosophical Look into the Future by Julian Vassyian - Daria Pohribna; Vadym Tytarenko (International Society of Philosophy and Cosmology, 2019)
The paper is devoted to further development of the criteria for identifying the Ukrainian nation. It is claimed that the effective strategy for such identification could be found in the theory of nation by the 20th-century Ukrainian philosopher Julian Vassyian. His main theoretical writings are focused on the "inner" factors which considered being crucial in terms of self-determination of the Ukrainian nation. In philosopher's opinion, the foreign policy factors are not as essential for the nation's self-identification as "inner" criteria, which are the national character, volitional activity and spiritual unity. He claimed that the definition of the objective "external" criteria such as language, territory, economic factors, etc. is not essential as well. The main principle of Ukrainian's national self-identification ought to be an awareness of being a representative of the nation and focus voluntary efforts on its development and improvement. Vassyian pays a lot of attention to the analysis of the main treats of the Ukrainian nation. Ukrainians should overcome the historically formed negative traits of the national mindset - peacefulness, defensiveness, excessive sentimentalism, social underdevelopment, etc. in order to become active subjects of the historical process. Ukrainian nation's formation mechanism is based on the triad "idea-will-aim." Vassyian's concept of "national genius" acts as a mechanism for activating and directing the individual's will to the formation of the nation. It is claimed that Vassyian's basic theoretical statements could be productively used by modern nation studies. In the authors' opinion, Vassyian's key ideas could contribute to the solution of current value-formation problems for the modern Ukrainian nation. It is asserted, that particular provisions of Julian Vassian's philosophy of Ukrainian nation could be helpful for the Ukrainian nation development in a modern globalised society.